(3JOGhd GdGhQGb GdeGdjI (B:s (3OQGSI bGfhfjI ebGQfI (B/s - (3ehdhO, YHO GdHGSW cQjes ((3HjQhJ(B: s (3efThQGJ GdMdHj GdMbhbjI(B, s, 2009)
(3ecGf h eMd JOGhd GdGhQGb GdeGdjI , eGgjI GdhSGWI aj JOGhd GdChQGb GdeGdjI , Mbhb h GdJRGeGJ hSjW GdGhQGb GdeGdjI , eGgjI YedjGJ GdHhQUI h bjO GdChQGb GdeGdjI ajgG , ChGeQ GdHhQUI , GdQbGHI Ydi YedjGJ GdJOGhd aj GdHhQUI , JOGhd GdChQGb GdeGdjI habG dfXGe GdGjOGY GdeQcRj (B: (3LgGJ GdGjOGY GdeQcRj , fTGWg h GdBKGQ GdeJQJHI Ydjgs
(3eQGLY U(B.613s
Keywords: (3GdCShGb GdeGdjI(B- (3GdHhQUGJs; (3GdChQGb GdeGdjIs